Testosterone Reduces Fear and Causes Drastic Hypomethylation of Arginine Vasopressin Promoter in Medial Extended Amygdala of Male Mice - Tong, Wen Han; Abdulai-Saiku, Samira; Vyas, Ajai (Frontiers in Behavioral Neuroscience, 2019)
Testosterone has been demonstrated to be an anxiolytic hormone. It reduces avoidance and enhances approach in ambivalent environments. However, effect of testosterone on innate fear such as fear of predators remains understudied. In this report, we demonstrate that testosterone reduces innate fear of predator odor. This manifests as an increase in time spent exploring the area containing cat odor when castrated male mice are supplemented with chronic exogenous testosterone. Congruently, we demonstrate that testosterone supplementation results in the hypomethylation of promoter region for arginine vasopressin gene in medial amygdala and bed nucleus of stria terminalis. Arginine vasopressin and its homologues are critical mediators of socio-sexual behavior in a range of species. Our results suggest that testosterone reduces innate aversion by co-opting pre-existing trade-off between fear and socio-sexual behaviors.